JENIS KUNANG-KUNANG (COLEOPTERA: LAMPYRIDAE) DI KAWASAN GUNUNG TUJUH, KABUPATEN KERINCI, PROVINSI JAMBI - Aulia, Annisa Izmi; Mairawita, Mairawita; Rahayu, Resti (Metamorfosa: Journal of Biological Sciences, 2017)
A study about firefly species was conducted at the Gunung Tujuh, Kerinci, Jambi Province. This study was used purposive sampling method and direct collection used insect net at Gunung Tujuh lake climb track. The results show that 59 individuals were collected consist of three subfamilies (Amydetinae, Lampyrinae and Luciolinae), six genera and 10 species. One species from Amydetinae are Vesta menetriesi , Lampyrinae were three species are Diaphanes javanus , Pyrocoelia analis and larvae of Lamprigera sp, and Luciolinae were six species are Curtos cerea , Curtos sp. 1, Curtos sp. 2, Luciola picea , Luciola sp. 1, and larvae of Luciola sp. 2. All species were not reported in previous studies in West Sumatra.